2009
DOI: 10.1116/1.3032904
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of bioconjugated core-shell CdSe∕ZnS quantum dots

Abstract: Articles you may be interested inSemiconductor core-shell quantum dot: A low temperature nano-sensor material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…The conjugation of biomolecules with QDs has been achieved, as a rule, through covalent bonds using functional groups (linkers) on the QD surface (Gerion et al, 2001;Parak et al, 2002;Wolcott et al, 2006) or with the help of electrostatic interaction between QDs and biomolecules in self-essembled cases (Clapp et al, 2004;Ji et al, 2005;Torchynska 2009a). The essential set of publications related to the study of QD bioconjugation using PL spectroscopy revealed that the PL intensity of QDs decreased (Guo et al, 2003;Ji et al, 2005;Torchynska et al, 2009a;Vega Macotela et al, 2010) or increased (Torchynska et al, 2009a;Torchynska et al, 2009b) owing, as supposed, to the energy exchange between QDs and biomolecules. The shape of PL spectra of these bioconjugated QDs was not changed (Guo et al, 2003;Ji et al, 2005;Torchynska et al, 2009a;Torchynska et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conjugation of biomolecules with QDs has been achieved, as a rule, through covalent bonds using functional groups (linkers) on the QD surface (Gerion et al, 2001;Parak et al, 2002;Wolcott et al, 2006) or with the help of electrostatic interaction between QDs and biomolecules in self-essembled cases (Clapp et al, 2004;Ji et al, 2005;Torchynska 2009a). The essential set of publications related to the study of QD bioconjugation using PL spectroscopy revealed that the PL intensity of QDs decreased (Guo et al, 2003;Ji et al, 2005;Torchynska et al, 2009a;Vega Macotela et al, 2010) or increased (Torchynska et al, 2009a;Torchynska et al, 2009b) owing, as supposed, to the energy exchange between QDs and biomolecules. The shape of PL spectra of these bioconjugated QDs was not changed (Guo et al, 2003;Ji et al, 2005;Torchynska et al, 2009a;Torchynska et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The size-tunable properties allow one to choose an emission wavelength that is well suited to experimental conditions and to synthesize the QD-based probe by using an appropriate semiconductor materials and nanocrystal sizes. In biology and medicine the semiconductor QDs have been used: for the fluorescence resonance energy transfer (FRET) analysis (Bailey et al, 2004;Jamieson et al, 2007;Zhang et al, 2005), in gene technology Han et al, 2001;Pathak et al, 2001), fluorescent labeling of cellular proteins (Dubertret et al, 2002;Dubertret et al, 2003;Hanaki et al, 2003), cell tracking (Bailey et al, 2004;Jamieson et al, 2007), pathogen and toxin detections (Lee et al, 1994;Yang et al, 2006), the bioconjugation to different antibodies and the targeted imaging and the delivery of anticancer drugs (Ebenstein et al, 2004;Ferrari et al, 2005;Torchynska 2009a;Torchynska et al, 2009b;Torchynska et al, 2010;Vega Macotela et al, 2010), the tissue, arterial and venous imaging (Larson et al, 2003;Wu et al, 2002), as well as in vivo animal imaging Parungo et al, 2005). The capping by wide band gap semiconductor (ZnS) of CdSe alone is not sufficient to stabilize the core, particularly in biological solutions, but the additional covering of ZnS shell with polymers or ZnS shell silanization provide increasing in QD stability and a reduction in non-specific adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…High energy PL bands (2.37, 2.73 and 3.06 eV) can be assigned to the recombination via: i) defects at the CdSe/ZnS interface; ii) excited states in the CdSe core or iii) defect states at the ZnS/polymer interface. The PL spectrum of non-conjugated CdSe/ZnS QDs has been studied at a low (10K) temperature (not shown) with the aim to clarify the nature of high energy PL bands [8][9][10]. The PL band related to exciton emission in the CdSe core shifted toward high energy (≈ 80-100 meV) due to the increase of CdSe optical band gap with temperature decreasing [8][9][10].…”
Section: Resultsmentioning
confidence: 98%
“…Raman scattering spectra were measured at 300 K by means of the spectrometer Lab-Raman HR800 Horiba Jovin-Yvon in the range of Raman shifts of 100-600 cm -1 at the excitation by a solid-state laser with a wavelength of 532 nm and a beam power of 20 mW [26,28]. The PL spectra of CdSe/ZnS QDs are characterized by the Gaussian shape PL band in the nonconjugated states with the peaks at 2.04 eV ( Figure 2) and 1.90 eV ( Figure 3) related to exciton emission in corresponding CdSe cores [31].…”
Section: IVmentioning
confidence: 99%
“…A set of publications, related to the study of QD bioconjugation using PL spectroscopy, revealed that the emission intensity of QDs decreased [12,24,25] or increased [22,26] owing to the energy exchange between the QDs and the biomolecules. Thus, the QD luminescence intensity depends on the concentration of attached biomolecules, promising the QD application as a protein sensor as well [6].…”
Section: Introductionmentioning
confidence: 99%